2021
DOI: 10.1016/j.bioactmat.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

An overview of filtration efficiency through the masks: Mechanisms of the aerosols penetration

Abstract: The masks have always been mentioned as an effective tool against environmental threats. They are considered as protective equipment to preserve the respiratory system against the non-desirable air droplets and aerosols such as the viral or pollution particles. The aerosols can be pollution existence in the air, or the infectious airborne viruses initiated from the sneezing, coughing of the infected people. The filtration efficiency of the different masks against these aerosols are not the same, as the particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
322
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(348 citation statements)
references
References 71 publications
(146 reference statements)
2
322
0
2
Order By: Relevance
“…The main criteria in this study was obtained from the systematic literature review stage and specified in two important characteristics, namely filtration efficiency and pressure drop or breathability. It was based on practical considerations for non-medical mask production by World Health Organization (2020) , and other study as in Chua et al (2020) , Aydin et al (2020) , Tcharkhtchi et al (2021) , Konda et al (2020) , and Zhao et al (2020) , as shown in Table S.2.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main criteria in this study was obtained from the systematic literature review stage and specified in two important characteristics, namely filtration efficiency and pressure drop or breathability. It was based on practical considerations for non-medical mask production by World Health Organization (2020) , and other study as in Chua et al (2020) , Aydin et al (2020) , Tcharkhtchi et al (2021) , Konda et al (2020) , and Zhao et al (2020) , as shown in Table S.2.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Studies about the use of face mask have been widely discussed from the material perspective, which investigates the alternative material that has the ability to capture particles and droplet (filtration efficiency), breathability and comfortability ( Aydin et al, 2020 ; Bagheri et al, 2020 ; Chua et al, 2020 ; Clase et al, 2020 ; Davies et al, 2013 ; Konda et al, 2020 ; Rengasamy et al, 2010 ; Rogak et al, 2020 ; Tcharkhtchi et al, 2021 ; Teesing et al, 2020 ; Wilson et al, 2020 ; Zhao et al, 2020 ), from the perspective of utility ( Howard et al, 2020 ; Lepelletier et al, 2020 ; Phan and Ching, 2020 ; Rubio-Romero et al, 2020 ; Wang et al, 2020 ; Yang et al, 2020 ) and after use impact ( Aragaw, 2020 ; Fadare and Okoffo, 2020 ; Ilyas et al, 2020 ; Vanapalli et al, 2021 ). Although, a lot of studies about face mask have been carried out for several months, the number of studies in material choice, especially those that considered the environmental impacts due to the waste is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these create a ‘dynamic collision trap’ as particles pass through the network of air channels between fibres at various speeds. 57 …”
Section: Introductionmentioning
confidence: 99%
“…The middle filter layer is most commonly made of polypropylene. Other types of protective equipment, P100 respirator/gas mask, self-contained breathing apparatus and full-face respirators are not commonly used by non-healthcare workers [8] .…”
Section: Introductionmentioning
confidence: 99%